COVID-19’s Effects over E-commerce: A Preliminary Statistical Assessment for Some European Countries - Campisi, Tiziana; Russo, Antonio; Tesoriere, Giovanni; Bouhouras, Efstathios; Basbas, Socrates (Computational Science and Its Applications - ICCSA 2021, 2021)
The advent of e-commerce has surged during the recent COVID-19 pandemic period. Already in 2019, many habits of users concerning online shopping platforms have changed: the age of those buying online has risen, the average income has fallen and the contagion has reached all urban and rural areas, even the smaller towns and villages. Since March 2020, when increased restrictions were applied, an increase in shopping of various kinds in several European and non-European countries is recorded. Many operators had to modify their logistics and change their interfaces. In short, the emergency has given a huge cultural boost to e-commerce. Tens of thousands of small retailers found themselves in the position of not being able to welcome consumers into their shops or being forced to create e-shops in a very short period of time and thus they identified home delivery as an opportunity not to be missed. Remote payment was the first, but not the only, effect. The present paper analyses the correlation between online shopping habits and socio-demographic characteristics in 27 European countries. The results were obtained from a descriptive statistical evaluation and the correlation between the variables was defined by the chi-square calculation. The results lay the foundations for the definition of the change in transport demand by home-purchase motivation and allow to define some considerations on the emission patterns that characterise transport demand.